Impact of Albuminuria and Renal Function on Ramadan Fasting in Type 2 Diabetes - Afandi, Bachar; Ahmedani, Yakoob; Boobes, Yousef; Bashier, Alaaeldin; Yousef, Sanobia; Ponirakis, Georgios; Malik, Rayaz A.; Alamoudi, Reem; Shaltout, Inass; Malek, Rachid; Hussein, Zanariah; Hafidh, Khadija; Hassanein, Mohamed (Journal of Diabetes and Endocrine Practice, 2025)
Diabetic kidney disease (DKD) is a common and serious complication, defined by albuminuria and/or reduced estimated glomerular filtration rate (eGFR).This study explored the impact of DKD and its subgroups on glycemic control and fasting safety during Ramadan.We analyzed data from the Diabetes and Ramadan Global Survey (2020–2022), including 12,529 participants with type 2 diabetes across seven regions. Participants were classified into four groups: no DKD (n = 10,780), DKD with albuminuria only (n = 460), DKD with low eGFR only (n = 1,150), and DKD with both albuminuria and low eGFR (n = 140). Outcomes included fasting patterns, hypoglycemia, hyperglycemia, and related interruptions.Most participants intended to fast (no DKD 86.5%, albuminuria only 80.0%, low eGFR only 76.4%, and albuminuria + low eGFR 80.6%). Mean fasting duration was ∼27 days across groups; however, those with reduced eGFR were more likely to fast only 1 to 7 days (6.4 vs. 2.4% without DKD, p < 0.0001). Daytime hypoglycemia occurred in 14.5% (no DKD), 19.0% (albuminuria only), 23.7% (low eGFR only), and 25.0% (albuminuria + low eGFR). Breaking fast due to hypoglycemia was more frequent in DKD groups (14.9–19.6 vs. 8.2% without DKD, p < 0.0001). Hyperglycemia was most frequent in albuminuria only (24.2%) and low eGFR only (18.4%) compared with no DKD (14.5%, p < 0.0001). Severe hyperglycemia was highest in low eGFR-only (2.0 vs. 0.8% without DKD, p < 0.001).Ramadan fasting is common among people with type 2 diabetes and DKD, but carries greater risks of both hypoglycemia and hyperglycemia. Albuminuria may signal reduced physiological resilience and glycemic stability, even when eGFR is preserved, while reduced eGFR confers the highest risk. Comprehensive pre-Ramadan assessment and tailored education are essential to support safer fasting in this high-risk population.
Keywords: Ramadan fasting; diabetic kidney disease; eGFR; albuminuria; hypoglycemia; hyperglycemia